2019
DOI: 10.1002/jcb.28648
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a three‐miRNA signature as a novel potential prognostic biomarker in patients with clear cell renal cell carcinoma

Abstract: Current studies suggest that some microRNAs (miRNAs) are associated with prognosis in clear cell renal cell carcinoma (ccRCC). In this paper, we aimed to identify a miRNAs signature to improve prognostic prediction for ccRCC patients.Using ccRCC RNA-Seq data of The Cancer Genome Atlas (TCGA) database, we identified 177 differentially expressed miRNAs between ccRCC and paracancerous tissue. Then all the ccRCC tumor samples were divided into training set and validation set randomly. Three-miRNA signature includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…9,10 The common characteristic of survival analysis modelling using microarray data is overfitting. 9,10 The common characteristic of survival analysis modelling using microarray data is overfitting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 The common characteristic of survival analysis modelling using microarray data is overfitting. 9,10 The common characteristic of survival analysis modelling using microarray data is overfitting.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many researchers focus on the exploration of microarray data. 9,10 The common characteristic of survival analysis modelling using microarray data is overfitting. Compared with the cox risk regression analysis, this imperfection can be perfectly solved by the least absolute shrinkage and selection operator (LASSO) cox method.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the heterogenous nature of kidney cancer (Sankin et al, 2014), single biomarker lacks ample credibility to predict patients' outcomes, thereby, an RS that is composed of more than one biomarker is necessary. There were a few former articles about ccRCC and RS models which were based on gene expression (Zeng et al, 2019;Li et al, 2018), lncRNA expression (Liu et al, 2018;Zhang et al, 2019) or miRNA expression (Luo et al, 2019;Fritz et al, 2014), because of the tremendous amount of genes and various RNAs the models of these studies were diverse. Currently, as the importance of m6A cut a striking figure, despite the fact that the first report of m6A was as early in 1974 (Desrosiers, Friderici & Rottman, 1974), it was not until recent days that the mechanism of the m6A was uncovered (Roundtree et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Various miRNAs have been revealed to play an important role in tumor carcinogenesis. A study reported that three independent prognostic miRNAs (hsa-mir-144, hsa-mir-21, and hsa-mir-155) participating in the competing endogenous RNA network in ccRCC [24]. A study based on TCGA database identified four miRNAs, miR-149-5p, miRNA-21-5p, miRNA-9-5p, and miRNA-30b-5p, as independent prognostic indicators in patients with ccRCC.…”
Section: Discussionmentioning
confidence: 99%